Impact of preparation method on nickel speciation and methane dry reforming performance of Ni/SiO2 catalysts - Chen, Chongchong; Wang, Wenbo; Ren, Qiuhe; Ye, Runping; Nie, Ning; Liu, Zhen; Zhang, Lulu; Xiao, Jinbin (Frontiers in Chemistry, 2022)
The methane dry reforming reaction can simultaneously convert two greenhouse gases (CH4 and CO2), which has significantly environmental and economic benefits. Nickel-based catalysts have been widely used in methane dry reforming in past decade due to their low cost and high activity. However, the sintering and coke deposition of catalysts severely limit their industrial applications. In this paper, three Ni/SiO2 catalysts prepared by different methods were systematically studied, and the samples obtained by the ammonia evaporation method exhibited excellent catalytic performance. The characterization results such as H2-TPR, XPS and TEM confirmed that the excellent performance was mainly attributed to the catalyst with smaller Ni particles, stronger metal-support interactions, and abundant Ni-O-Si units on the catalyst surface. The anti-sintering/-coking properties of the catalyst were significantly improved. However, the Ni/SiO2-IM catalyst prepared by impregnation method had uneven distribution of nickel species and large particles, and weak metal-support interactions, showing poor catalytic performance in methane dry reforming. Since the nickel species were encapsulated by the SiO4 tetrahedral network, the Ni/SiO2-SG catalyst prepared by sol-gel method could not expose more effective active sites even if the nickel species were uniformly dispersed, resulting in poor dry reforming performance. This study provides guidance for the preparation of novel anti-sintering/-coking nickel-based catalysts.